Neufassung der Stellungnahme der DGRh zu Biosimilars - Update 2017 = Revised version of the statement by the DGRh on biosimilars - update 2017 - Braun, Jürgen; Lorenz, Hanns-Martin (Zeitschrift für Rheumatologie, 2018)
The treatment of rheumatic diseases with bioloics has significantly improved the prognosis of patients. Currently, there are 13 preparations available in Germany for the treatment of patients with inflammatory rheumatic diseases. These original preparations generally have—depending on the individual country—15 years of patent protection. As soon as the patent has expired, approved biosimilars can be brought into use. For the approval of a biosimilar, authorities such as the European Medical Agency or the American Food and Drug Administration require proof of the best possible comparability with respect to efficacy and safety in comparison to the original or reference product. Since 2015, biosimilars of inifliximab, adalimumab, etanercept and rituximab have been granted approval in the European Union, the USA, Japan and in other countries. Further biosimilar products for these reference products are in development for treatment in rheumatology. From a societal and medical point of view, this opens up the possibility to increase the availability of biopharmaceutical products for patients through lower prices. In Germany, this possibility has already occurred—statutory health insurance physicians have introduced quotas for biosimilars, which will ultimately decrease spending and healthcare costs. This can lead to price reductions of the original products, which has already happened in Germany. Biosimilars can be prescribed for new patients or as a change from the original to the generic drug. When switching, a distinction is made between individual switching (interchangeability), which is made in individual consultation between the physician and the patient, and nonmedical switching (substitution) made at the societal or governmental level, which is made in the context of health care cost containment, and then, for example, implemented at the pharmacy level. Preliminary data from Norway and Denmark are available for substitution on the basis of results from large studies or registries in which systematic changes were made. The previous conclusion was that this does not lead to new problems for the patients. The German Society for Rheumatology recognizes the advantages of introducing biosimilars in Germany, but recommends that their use be based primarily on a joint decision by the treating physician and patient.